An Analytical Target Profile for the Development of an In Vitro Release Test Method and Apparatus Selection in the Case of Semisolid Topical Formulations - Réka Szoleczky; Anita Kovács; Szilvia Berkó; Mária Budai-Szűcs (MDPI AG, 2024)
This study focuses on how to define an Analytical Target Profile (ATP) which is intended for use in practice and on facilitating the selection of in vitro release test (IVRT) technology for diclofenac sodium topical hydrogel and cream. The implementation involves incorporating the new draft guidelines of the International Council for Harmonisation (ICH Q14) and USP (United States Pharmacopeia) Chapter 1220. Four IVRT apparatuses were compared (USP Apparatus II with immersion cell, USP Apparatus IV with semisolid adapter, static vertical diffusion cell, and a new, in-house-developed flow-through diffusion cell) with the help of the ATP. Performance characteristics such as accuracy, precision, cumulative amount released at the end of the IVRT experiment, and robustness were investigated. We found that the best apparatus for developing IVRT quality control (QC) tests in both cases was USP II with an immersion cell. All four different IVRT apparatuses were compared with each other and with the data found in the literature.